Study of Drug Use and Evaluation of Paracetamol-Diazepam Mixed Capsule Preparations - havizur rahman; Dyah Ayu Mulya Patmasari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
The purpose of this study was to predict the potential effect of theoretical use and evaluation of Paracetamol and Diazepam capsules concoction preparation in poly-nerve patients in outpatient depot Pharmacy Installation of Raden Mattaher Hospital. Methods of data collection used observation techniques with retrospective study data collection techniques. It was found that 12 patients used the Paracetamol 500 mg concoction capsules and 0.5 mg Diazepam given twice a day, used every day with a minimum usage period of 1 month and a maximum of 56 months, 5 of whom were over 60 years old. The capsule concoction that is made is not derived from the pure active ingredient of Paracetamol and Diazepam, but is a trademark tablet drug which is crushed without BA and BE evaluation of the concoction form. So, it can be concluded that the use of Paracetamol and Diazepam concoction capsules is predicted to pose a risk of causing hepatotoxic and physical and psychological dependence and capsule concoction drugs that are made do not meet the criteria set by the FDA.